Liquidity analysis of innovative and traditional businesses in Poland - Bolek, Monika; Grosicki, Bartosz (Business, Management and Economics Engineering, 2012)
This paper analyzes the liquidity of Polish non-financial companies listed on the Warsaw Stock Exchange, dividing them into two groups: companies with the intangible to fixed assets ratio higher than the median, deemed to be innovative businesses, and companies with the intangible to fixed assets ratio lower than the median, deemed to be traditional businesses. Our results show that liquidity management is different in these two groups when analyzing the cash conversion cycle, the current and quick ratios, and liquid assets. The authors use data representing the Polish economy on the assumption that it can be considered a model one for other developing countries. Poland is at the beginning of this road, completing its systemic transformation after 20 years of efforts, as society has been building an innovation-based economy. Skills in the field of financial management will have to be developed as data analysis described in this paper reveals poor liquidity management. The authors will follow the development of the Polish economy (called a European tiger) to show how it has changed over time.